ISSUES AND CHALLENGES IN MAINTAINING MOTIVATION TO LEARN ENGLISH IN RURAL MADRASAH CONTEXT - Mochammad Imam Machfudi (IJET (Indonesian Journal of English Teaching), 2016)
Issues and challenges in teaching English in rural madrasahs are enormous. Despite the fact that English is considered to be a difficult subject, its presence as a compulsory subject does not seem desirable in such a situation. In this socio-cultural context, maintaining motivation is an important element among the challenges where the students are not motivated to learn English. This article explains the issues and challenges and the motivational strategies developed by Madrasah Tsanawiyah teachers of English in teaching English in their context and the impact on their students. By analysing the teachers’ lived-experience through their stories this research finding shows that there are three kinds of motivational strategies enacted by the teachers of English in the rural areas of East Java including giving rewards, positive feedback, and increasing self-esteem and self-confidence. These three elements of external motivation indicate that the motivation plays a significant role in engaging students to learn English.